Analysis of Powder Properties and Pharmacopeial Spesifications of Bagasse Cellulose Isolated from Saccharum Officinarum L in Indonesia - Begum Fauziyah; Mohammad Yuwono; Isnaeni (Indian Journal of Forensic Medicine & Toxicology, 2021)
Saccharum Officinarum L is native to Asian countries, including Asia. Indonesia is the third-largest sugarcane producer in the ASEAN region. The amount of sugarcane production represents the potential amount of bagasse waste obtained. Bagasse has not been used properly and optimally in Indonesia. Bagasse contains 43.6% cellulose; hemicellulose 33.8%; lignin 18.1%; ash 2.3% and wax 0.8%. The purpose of this study was to isolate bagasse cellulose with 5% of nitric acid. We determined the organoleptic powder properties and pharmacopeial specifications of bagasse cellulose as pharmaceutical raw materials. As a result, the test parameters as pharmaceutical raw materials for bagasse cellulose met the requirements compared to Japan Pharmacopeia XV except for the ash content value. Bagasse cellulose powder had a white color, a water content of 5.93%, and pH 6.7. It was insoluble in water-ethanol and ether and had Pb-Cr-Cd metal content <10 ppm. The microbial limits were below the specified requirements. The ash content was 0.6, the bulk density was 0.136, the tapped density was 0.158, Carr’s index was 13.92, the Hausner ratio was 1.162, and the angle of repose was 56.4. Based on the angle of repose value, bagasse cellulose powder had fairly good flow properties.